The ancient commentators of Plato and Aristotle - Tuominen, Miira (Acumen, 2009)
In late antiquity the works of Plato and Aristotle were subject to intense study, which eventually led to the development of a new literary form, the philosophical commentary. Until recently these commentaries were understood chiefly as sources of information for the masters, Plato and Aristotle, they commented upon. However, in recent years, it has become increasingly acknowledged that the commentators themselves - Aspasius, Alexander, Themistius, Porphyry, Proclus, Philoponus, Simplicius and others - even though they worked in the Platonist-Aristotelian framework, contributed to this tradition in original, innovative and significant ways such that their commentaries are philosophically important sources in their own right. This book provides the first systematic introduction to the philosophy of the commentators: their way of doing philosophy and the kind of philosophical problems they found interesting. The book begins with an examination of the commentary method as a way of practising philosophy, the commentators own understanding of their task, and why the philosophical commentary emerged as it did. The central chapters then explore the most important philosophical themes that occupied the commentators: questions concerning the nature and justification of knowledge, the nature of the soul, questions about the explanation of change in nature as well as cosmological discussions about whether the world is eternal or created. These discussions lead to a treatment of the metaphysical assumptions behind the psychology and epistemology of the commentators, the development of the metaphysical doctrines themselves, and, finally, to the question how the commentators developed the ethical doctrines of their predecessors. In her discussion of these key themes, Miira Tuominen shows how the commentators formulation of philosophical problems can be understood in the framework of similar contemporary problems and in so doing helps integrate the commentators into the same continuum of thinkers who have worked in different historical periods and employed different methods. Although there was no philosophy of the commentators in the sense of a definite set of doctrines, Tuominen shows how the commentary format was nevertheless a vehicle for original philosophical theorizing and argues convincingly that the commentators should take their place alongside other philosophers of antiquity in the history of western philosophy.